The nanny diaries - Gladstein, Richard N.; Wolf, Dany.; Berman, Shari Springer; Pulcini, Robert; Johansson, Scarlett, 1984-; Linney, Laura; Giamatti, Paul.; Evans, Chris, 1981-; Keys, Alicia; McLaughlin, Emma.; Kraus, Nicola; Weinstein Company; et al. ([New York] : Weinstein Company ; Santa Monica, Calif. : Distributed by Genius Products, 2007)
Annie is a young girl from a working-class neighborhood who suddenly finds herself working as a nanny for a wealthy family in Manhattan's Upper East Side. Between catering to the every whim of her employers and their son and falling in love with their gorgeous neighbor, Annie tries to figure out what she wants to do with her life.
Based on the novel by Emma McLaughlin & Nicola Kraus.
Special features: Life at the top as seen from the bottom : the making of 'The Nanny Diaries'; Confessions from the original nannies : the authors of the bestselling book; bloopers; theatrical trailer.
Director of photography, Terry Stacey ; edited by Robert Pulcini ; music by Mark Suozzo ; costume designer, Michael Wilkinson ; production designer, Mark Ricker.
Scarlett Johansson, Laura Linney, Alicia Keys, Donna Murphy, Paul Giamatti, Chris Evans.
MPAA rating: PG-13; for language.
DVD; English track: Dolby digital 5.1.
Keywords: Nannies -- New York (State) -- New York -- Drama; Upper class families -- New York (State) -- New York -- Drama; Man-woman relationships -- New York (State) -- New York -- Drama; Upper East Side (New York, N.Y.) -- Drama; Feature films; Comedy films; Films for the hearing impaired